2011
DOI: 10.1016/j.janxdis.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in PTSD symptoms: An exploration of peritraumatic mechanisms

Abstract: Females are at higher risk than males for developing posttraumatic stress disorder symptoms (PTSS) following exposure to trauma, which may stem from gender differences in initial physiological and psychological responses to trauma. The present study aimed to examine a number of peri- and initial post-traumatic reactions to motor vehicle accidents (MVAs) to determine the extent to which they contributed to gender differences in PTSS. 356 adult MVA survivors (211 males and 145 females) reported on peritraumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 58 publications
11
83
3
Order By: Relevance
“…Moreover, women reported higher anxiety and perceived impact of either events than men. This is in line with studies showing that women report higher levels of perceived life threat after traumatic A1 events which is predictive of posttraumatic distress (Irish et al, 2011) and might be associated with lower levels of perceived control in women compared to men after A1 events (e.g. Mak, Blewitt, & Heaven, 2004; Olff et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, women reported higher anxiety and perceived impact of either events than men. This is in line with studies showing that women report higher levels of perceived life threat after traumatic A1 events which is predictive of posttraumatic distress (Irish et al, 2011) and might be associated with lower levels of perceived control in women compared to men after A1 events (e.g. Mak, Blewitt, & Heaven, 2004; Olff et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Some studies indeed suggest that these initial responses to trauma may account for gender differences in PTSD (e.g. Irish et al, 2011), but a review by Olff et al (2007) emphasizes that there is a serious lack of evidence on gender specific appraisal processes of trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the presence of negative peritraumatic emotions (e.g., fear, horror and helplessness) and PD were predictive of PTSD onset in VVC (Brewin, Andrews Rose, 2000b;Elklit & Brink, 2004). A more recent investigation on MVA survivors showed that PD predicted PTSD 6 months later but was not a significant predictor of ASD (Irish et al, 2011). The current study confirms the importance of addressing peritraumatic reactions in VVC.…”
Section: Peritraumatic Responses Are Associated With Ptsd Among Victisupporting
confidence: 80%
“…PD was further found to account for gender differences in PTSD development within the same population (Irish et al, 2011).…”
Section: Introductionmentioning
confidence: 87%
“…Some researchers have argued that, rather than differences in trauma exposure, differences in cognitive factors, such as trauma memory records or self-schemas, contribute to a higher prevalence of PTSD among women, as these may affect the manner in which individuals process, recall, and respond to traumatic experiences (Simmons & Granvold, 2005). Indeed, there is evidence that gender differences in acute responses to trauma contribute to subsequent gender differences in PTSD (Irish et al, 2011). As such, women would experience higher levels of PTSD regardless of the number of traumatic experiences they had, resulting in a generalized increased risk of developing PTSD, rather than an increasing vulnerability as the number of traumatic experiences increases.…”
Section: Discussionmentioning
confidence: 99%